The ark plan - Martin, Laura; Galvin, Emma (New York : Harper Audio, 2016)
A century and a half after cloned dinosaurs forced humans to move into underground compounds, Sky discovers a clue to the whereabouts of her long-missing father and ventures above ground on a quest that has the potential to save the world.
3-6
OBOB 2019-2020.
6 compact discs.
Keywords: Friendship -- Juvenile fiction; Dinosaurs -- Juvenile fiction; Survival -- Juvenile fiction; Friendship -- Fiction; Dinosaurs -- Fiction; Survival -- Fiction; Action and adventure fiction; Audiobooks